Characterization of Iranian Olive Oils based on Biophenolic Minor Polar Compounds and their Contribution to Organoleptic Properties - Forough SHAVAKHI; Anosheh RAHMANI; Parviz MORADI (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
The presence of several minor compounds, such as biophenols, are associated with the quality, health benefits and sensory characteristics of olive oil. The objectives of this study were to compare the profile of the individual phenolic compounds of major brands of olive oils produced in Iran and to correlate the minor polar biophenolic compounds with sensorial properties and finally discriminate the samples. In order to define similarities and differences between Iranian virgin olive oils, profiles of their biophenolic compounds have been investigated using HPLC, analysis of variances and principal component analysis (PCA). Samples of olive oil were notably varied in terms of individual biophenolic compounds and total phenolic content (TPC). Hydroxytyrosol, tyrosol, oleuropein, luteolin, apigenin, and ligstroside aglycone (aldehyde and hydroxylic form) were detected in all samples, whereas caffeic acid was not found in any brands. Based on the differentiating made by PCA, samples were categorized into two distinct groups (TPC<300 and TPC>300 mg tyrosol/kg of olive oil). The analysis of the main components resulted in a model that describes 86% of the total variance discriminating them from the minor biophenolic compounds of the examined olive oils. This analysis can be considered for assessing the quality and commercial needs related to preferences on olive oil.